2013
DOI: 10.1089/hum.2012.202
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Hematopoietic Stem/Progenitor Cells with CD19-Specific Chimeric Antigen Receptors as a Novel Approach for Cancer Immunotherapy

Abstract: Chimeric antigen receptors (CARs) against CD19 have been shown to direct T-cells to specifically target B-lineage malignant cells in animal models and clinical trials, with efficient tumor cell lysis. However, in some cases, there has been insufficient persistence of effector cells, limiting clinical efficacy. We propose gene transfer to hematopoietic stem/progenitor cells (HSPC) as a novel approach to deliver the CD19-specific CAR, with potential for ensuring persistent production of effector cells of multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 43 publications
3
88
0
Order By: Relevance
“…22 However, there is also potential for the use of multilineage effector cells when hematopoietic stem cells or other precursor cells are used as the starting cell type. [64][65][66] Defining the phenotype or active ingredient of these cell types will be even more challenging than T cells. Finally, NK cells can also be powerful effector cells, and some investigators have transduced NK cells with second-generation CARs.…”
Section: Future Outlook Manufacturingmentioning
confidence: 99%
“…22 However, there is also potential for the use of multilineage effector cells when hematopoietic stem cells or other precursor cells are used as the starting cell type. [64][65][66] Defining the phenotype or active ingredient of these cell types will be even more challenging than T cells. Finally, NK cells can also be powerful effector cells, and some investigators have transduced NK cells with second-generation CARs.…”
Section: Future Outlook Manufacturingmentioning
confidence: 99%
“…Other groups have also suggested that where the CAR binds the target antigen (i.e., membrane proximal vs. distal epitopes) [4] and/or the length of the linker sequence [5][6][7] are important considerations in optimizing CAR design. Here, our attention has also recently been drawn to the spacer or hinge sequences that are used to link the ligand-binding domain to transmembrane and intracellular-signaling domains of the CAR -specifically the use of immunoglobulin Fc spacers commonly applied to CAR design [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Our data now also suggest that the sequences that are known as either the spacer, hinge and/or linker used to connect the ligand-binding domain to the signaling domain(s) of the CAR is of previously unappreciated importance for in vivo therapeutic outcome in murine models of malignant disease. Specifically, we have found that the use of an Ig Fc spacer -which has been included in CARs designed by our group and others[8][9][10][11][12][13][14][15][16] -can potentially inhibit the engraftment and/or persistence of CAR-expressing cells in NSG mouse models in a manner that correlates with Fc R binding. This lack of engraftment can be partially rescued by IVIG administration which is anticipated to compete for FcRmediated binding.…”
mentioning
confidence: 98%
“…It has also been suggested to develop inhibitory CARs with the aim of dampening T-cell activation in the presence of an antigen expressed on normal cells, while allowing T-cell activation via a separate CAR [96]. Another therapeutic strategy consists in the development of new types of CAR T-cells, including universal CAR T-cells and hematopoietic stem cell derived CAR T-cells [97]. Universal CAR T-cells are made from healthy donor T cells and do not depend upon patients' lymphocytes.…”
Section: Expert Opinionmentioning
confidence: 99%